Consideraciones jurídicas acerca de la del uso de la anticoncepción oral de emergencia en Costa Rica - Soto Prats, Bárbara Eva (2015)
A criticism is made due to the lack of regulation from thesanitary authorities about the subject of emergency contraception. Themechanisms of action of the emergency contraception are approachedfrom an objective analysis, to finally give the authors’ opinion about themorning after pill